Development and psychometric testing of the 10-item satisfaction with Nursing Skill Examination: Objective Structured Clinical Assessment scale. (May 2020) - Hunt, Leanne; Ramjan, Lucie M.; Daly, Miranda; Lewis, Peter; O'reilly, Rebecca; Willis, Sue; Salamonson, Yenna
Abstract: The Objective Structured Clinical Examination (OSCE) or Assessment (OSCA) has traditionally been used in disciplines such as medicine and nursing, to assess students' competence to perform clinical skills safely in a simulated hospital environment. Despite its accepted use, a validated and reliable tool has yet to be developed and tested to assess students' perception of and satisfaction with this mode of assessment. This study developed and tested the psychometric properties of a brief Objective Structured Clinical Examination tool for assessing student perception that could have transferability across health education settings. The study used a cross-sectional survey design. Final year students ( n = 727) enrolled in an undergraduate nursing program in Western Sydney completed the 10-item Satisfaction with Nursing Skill Examination: Objective Structured Clinical Assessment (SINE-OSCA) Scale in 2017. Exploratory factor analysis uncovered a one-component structure with component loading that ranged from 0.45 to 0.86. Cronbach's alpha of the SINE-OSCA was 0.91. Socio-demographic group comparisons revealed that respondents who were: i) male ( p = 0.003); ii) non-native-born ( p < 0.001); iii) non-English-speaking ( p < 0.001); and iv) International ( p = 0.001), reported higher satisfaction with clinical assessments, as measured by the SINE-OSCA scale. The SINE-OSCA scale demonstrates validity and reliability in identifying students who may have difficulty with this mode of clinical skill assessment. Highlights: Assessment of clinical competence has moved toward competency-based assessment. OSCA is a quality check prior to clinical placement. There is increasing diversity among undergraduate nursing students. A "one size fits all" approach to assessment may not suit all students.